KETIMPANGAN SOSIAL DALAM NOVEL BURUNG BERPAGUT EMAS KARYA M. SJOHIRIN - Tri Febriana Karuniawati; Eggy Fajar Andalas (Universitas Muhammadiyah Surakarta, 2022)
Burung Berpagut Emas is a literary work that provides an overview to the reader about theproblem of social inequality. This work represents the social problems that occur, especially inurban and rural communities. This study aims to describe the picture of social inequalitybetween urban and rural communities depicted in the novel. This research is a descriptivequalitative type with a sociological approach to literary works. The data were collected by usingthe look-note technique. The analysis technique used is content analysis. The results of theresearch show that in the novel Burung Berpagut Emas, social inequality between urban andrural communities is described in three aspects, namely economic, social, and power. Inequalitythat occurs has resulted in the emergence of a stigma in society that the village community is atraditional society, low, less competitive, left behind. On the other hand, the stigma in urbancommunities is that they are rich, capital owners, advanced, and modern. It can be concludedthat this work records social realities that occur in Indonesia. This work does not only recordsocial problems that occur in society, but provides critical awareness to readers regarding socialproblems that must be resolved.Keywords: social inequality, sociology of literary works, social stratification